A Theoretical Study on Nonlinear Bending of Wires - Baragetti, S. (Meccanica (Milan), 2006)
The nonlinear bending of thin wires is a challenging topic in several applications where the final geometry of the wire after bending and springback has to be known. Typical examples are tyre manufacturing, helical spring design, spectacles frames. In order to develop analytical models able to set bending parameters for a required final shape of the wire, both account material behaviour (during the loading and unloading phases with springback effect) and geometrical nonlinearity have to be considered. In the case of plates bending, many analytical and numerical models are available in the literature, offering an accurate solution to this problem. However, the bending of thin wires could still be the subject of discussion and research. In this paper a new analytical model was developed, starting from the models available in the literature, in order to provide the designer with a simple model to predict the final shape of a wire by using mathematical codes. The model allows to predict with a higher level of accuracy the final shape of wires having different cross-sections after nonlinear bending. Since Bernoulli's hypothesis is assumed, the model can be used in all the applications where the material behaviour of the wire guarantees that plane cross sections of the wire will remain plane after rotation due to bending, with negligible errors from the engineering point of view.